2020
DOI: 10.33448/rsd-v9i7.4391
|View full text |Cite
|
Sign up to set email alerts
|

Physical chemical characterization, bioactive compounds and antioxidant activity of Pachira aquatica Aublet almonds

Abstract: The Pachira aquatica Aublet, belonging to the Malvaceae family, is a tree of variable size, annually produces large quantities of capsule type fruits, in which its seeds remain stored. Even though it is commonly found in southern Mexico and Brazil, there are few studies on its composition. Therefore, the objective of this study is to demonstrate the characteristics of this fruit by means of physical analyzes and to evaluate the bioactive compounds of the almonds in the raw, cooked and roasted forms. Type of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Munguba butter has a solid appearance at room temperature, yellowish color and characteristic odor. Furthermore, studies have reported the presence of γ-tocopherol, phytosterols and flavonoids, bioactive compounds that perform important functions such as antioxidant, anti-inflammatory and anti-hyperglycemic actions, in addition to preventing cardiovascular diseases (Rodrigues and Pastore, 2021;Silva et al, 2020;Lopes et al, 2020), demonstrating potential application in the development of new food, pharmaceutical and cosmetic products. Nanoemulsified system containing bacaba peel extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munguba butter has a solid appearance at room temperature, yellowish color and characteristic odor. Furthermore, studies have reported the presence of γ-tocopherol, phytosterols and flavonoids, bioactive compounds that perform important functions such as antioxidant, anti-inflammatory and anti-hyperglycemic actions, in addition to preventing cardiovascular diseases (Rodrigues and Pastore, 2021;Silva et al, 2020;Lopes et al, 2020), demonstrating potential application in the development of new food, pharmaceutical and cosmetic products. Nanoemulsified system containing bacaba peel extract.…”
Section: Discussionmentioning
confidence: 99%
“…Munguba butter is predominantly composed of saturated fatty acids, mostly palmitic, and has important properties derived from bioactive compounds such as vitamin E and phytosterols (Rodrigues and Pastore, 2021). Therefore, some studies have evaluated the presence of phenolic compounds and the antioxidant activity of munguba butter (Rezende et al, 2021;Rodrigues et al, 2019;Raiser et al, 2020;Silva et al, 2020), valorizing its application in developing new products. Raiser et al (2018), when developing a cosmetic cream containing munguba butter observed stability at room temperature, maintenance of pH close to the skin's pH, and good spreadability of the product, in addition to antioxidant activity suggesting the use of munguba butter as an alternative to synthetic antioxidants.…”
Section: Rheological Characterizationmentioning
confidence: 99%